2018 25th IEEE International Conference on Image Processing (ICIP) 2018
DOI: 10.1109/icip.2018.8451386
|View full text |Cite
|
Sign up to set email alerts
|

Deep Learning Based Supervised Semantic Segmentation of Electron Cryo-Subtomograms

Abstract: Cellular Electron Cryo-Tomography (CECT) is a powerful imaging technique for the 3D visualization of cellular structure and organization at submolecular resolution. It enables analyzing the native structures of macromolecular complexes and their spatial organization inside single cells. However, due to the high degree of structural complexity and practical imaging limitations, systematic macromolecular structural recovery inside CECT images remains challenging. Particularly, the recovery of a macromolecule is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
2
2
1

Relationship

4
4

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 25 publications
0
13
0
Order By: Relevance
“…This encoder-decoder variant of the FCN adds skip connections in the upsampling phase that combines the higher layers with the lower pooling layers to fully utilize global context information while integrating the local information to accurately map low-resolution images to voxel-wise predictions. In a previously published paper, it is found that this model has consistently outperformed other similar variants of FCNs for the segmentation task [7]. Our simulation provides 3D simulated cryo-ET data that can serve as the training data for EDSSN3D network and reduce the amount of training data preparation required of this model and thus successfully break the originally thought trade-off between accuracy and data preparation.…”
Section: Test Of Semantic Segmentation Methods Using Fully Convolutionmentioning
confidence: 65%
See 1 more Smart Citation
“…This encoder-decoder variant of the FCN adds skip connections in the upsampling phase that combines the higher layers with the lower pooling layers to fully utilize global context information while integrating the local information to accurately map low-resolution images to voxel-wise predictions. In a previously published paper, it is found that this model has consistently outperformed other similar variants of FCNs for the segmentation task [7]. Our simulation provides 3D simulated cryo-ET data that can serve as the training data for EDSSN3D network and reduce the amount of training data preparation required of this model and thus successfully break the originally thought trade-off between accuracy and data preparation.…”
Section: Test Of Semantic Segmentation Methods Using Fully Convolutionmentioning
confidence: 65%
“…In the fields of protein visualization and structural biology, various machine learning methods are applied to the analyse the structure of macromolecules and ultrastructures [5][6][7]. These methods can resolve the structure of macromolecules to a large extent, but the accuracy still need to be improved.…”
Section: Introductionmentioning
confidence: 99%
“…This network design allows the training of the three tasks to mutually reinforce each other for better feature extraction and therefore higher accuracy. The accuracy of this model for classification and semantic segmentation outperformed single-task models (10,11).…”
Section: Simultaneous Classification and Segmentation By Multi-task Lmentioning
confidence: 93%
“…Two 3D semantic segmentation convolutional neural networks (SSN3D) and their variants segmenting the main structural region from subtomograms have been proposed (10). This is a very useful step in subtomogram analysis because masking out neighboring structures can significantly reduce the structural bias for further analysis such as averaging and classification.…”
Section: Semantic Segmentation Using Convolutional Neural Networkmentioning
confidence: 99%
“…CNN [17] are well-known for extracting features from a image by using convolutional kernels and pooling layers to emulates the response of an individual to visual stimuli. This work [20] is the first application of deep learning for systematic structural discovery of macromolecular complexes among large amount (millions) of structurally highly heterogeneous particles captured by Cryo-ET. It represents an important step towards large scale systematic detection of native structures and spatial organizations of large macromolecular complexes inside single cells.…”
Section: A Cryo-electron Tomography (Cryo-et)mentioning
confidence: 99%